Child Protection in Formal ECE: Regulatory Coherence and Service Readiness in Indonesia - Hamid Patilima (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
Child protection in formal early childhood education is rarely examined through the lens of regulatory coherence, even though safe provision depends on clear rules, procedures, and service coordination. This study analysed the coherence of the national legal and policy framework for child protection in formal ECE and interpreted its implications for service readiness. A qualitative policy analysis with directed document review was conducted on 22 sources published or adopted between 2005 and 2026. Data were extracted into an analytical matrix and coded against six service-readiness indicators. The review found a strong normative foundation and showed that the 2026 education regulations clarified prevention, reporting, complaint handling, referral, and institutional coordination, although workforce readiness and cross-service operational integration remained uneven. Child protection should therefore be positioned as a core component of quality assurance and governance in formal ECE.